Bright and singular soliton solutions of the conformable time-fractional Klein–Gordon equations with different nonlinearities. Issue 3 (3rd July 2018) - Hosseini, Kamyar; Mayeli, Peyman; Ansari, Reza
Abstract: Finding the exact solutions of nonlinear fractional differential equations has gained considerable attention, during the past two decades. In this paper, the conformable time-fractional Klein–Gordon equations with quadratic and cubic nonlinearities are studied. Several exact soliton solutions, including the bright (non-topological) and singular soliton solutions are formally extracted by making use of the ansatz method. Results demonstrate that the method can efficiently handle the time-fractional Klein–Gordon equations with different nonlinearities.